The Effect of Osteoporosis Risk Factors on Bone Mineral Density - Ebru Umay; Uğur Tamkan; İbrahim Gündoğdu; Serkan Umay; Aytül Çakcı (Galenos Yayinevi, 2011)
Introduction: This study aimed to evaluate whether osteoporosis (OP) risk factors have any effect on bone mineral density in patients receiving OP treatment. Material and method: The study included 73 postmenopausal women with OP who had been using bisphosphonate treatment for one year, with at least one of either total lumbar or femoral neck T-score still <-2.5 and whose total lumbar and/or femoral neck T-scores showed no improvement compared to one year earlier. Demographic characteristics and OP risk factors were recorded. Mini-mental test (MMT), Beck Depression and Anxiety Scales were used in the evaluation of the cognitive status of patients. The assessed parameters of patients were compared with the current total lumbar and femoral neck T-scores. Results: Being underweight, illiteracy, high gravidity, inadequate calcium intake, and cognitive dysfunction were found to be effective on lumbar and femoral neck T- scores, while tea and coffee consumption, smoking status and the presence of additional comorbidity and drug use were found to be effective on femoral neck T-scores. Conclusion: Some OP risk factors may contribute to the ineffectiveness in patients receiving regular OP treatment who fail to show adequate response. (Turkish Journal of Osteoporosis 2011;17:44-50)